Pengaruh Gender Dan Uang Saku Terhadap Tingkat Literasi Keuangan Siswa Kelas XI Akuntansi SMK Negeri 1 Seririt - Dewi, Komang Tri Sitha; Suwena, Kadek Rai (Universitas Pendidikan Ganesha, 2023)
Research in this case is aimed at determining the partial influence of gender and pocket money on the level of financial literacy of class XI accounting students of SMK Negeri 1 Seririt, as well as determining the simultaneous influence of gender and pocket money on the level of financial literacy of class XI accounting students of SMK Negeri 1 Seririt. This study is classified as a causal study. The research population, namely class XI students of SMK Negeri 1 Seririt majoring in Accounting, was 66 people. The total sampling technique was used as a sample determinant in this study, so that the entire population was a sample. Questionnaire instruments are used in the method of data collection. Multiple linear regression analysis is used as a tool to obtain research objectives with a t-test and an f-test as a hypothesis test. Based on data analysis, results were obtained, namely (1) gender has a significant effect on students' financial literacy levels, (2) pocket money has a significant effect on students' financial literacy levels, (3) gender and pocket money simultaneously have a significant effect on students' financial literacy levels.